A 2-Gene Signature Related to Interferon-Gamma Predicts Prognosis and Responsiveness to Immune Checkpoint Blockade of Glioma - Li, Yongzhe; Ji, Hang; Gao, Xin (Frontiers in Medicine, 2022)
Background: Gliomas represent the most common and aggressive brain malignancy. Interferon-gamma (IFNG) is a paramount immune regulator in the tumor microenvironment, developing IFNG-related gene signature may promote the diagnosis and treatment of this disease. Methods: Bulk tumor and single-cell mRNA-seq datasets of glioma ranging from WHO grade II to IV with corresponding demographics were included. Multiple bioinformatics and machine learning algorithms were performed to develop an IFNG-related prognostic signature and evaluate immune checkpoint blockade therapy response. Results: The IFNGR score representing the expression of IFNGR1 and IFNGR2 well-characterized the IFNG response in the glioma microenvironment. Increased IFNGR score was associated with clinicopathological parameters relating to tumor malignancy and prevailing molecular pathological markers. Notably, K-M and Cox regression analysis found that the IFNGR score was an effective prognostic biomarker, and was associated with tumor relapse for a subset of patients. Moreover, the IFNGR score-based group had the potential to predict ICB responsiveness, as effectively as previously validated IFNG-related gene signatures. Conclusion: In conclusion, we have developed a concise IFNG-related gene signature of clinical significance, which may improve the current diagnosis and treatment of glioma.